-6=-2c-18

Simple and best practice solution for -6=-2c-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=-2c-18 equation:


Simplifying
-6 = -2c + -18

Reorder the terms:
-6 = -18 + -2c

Solving
-6 = -18 + -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
-6 + 2c = -18 + -2c + 2c

Combine like terms: -2c + 2c = 0
-6 + 2c = -18 + 0
-6 + 2c = -18

Add '6' to each side of the equation.
-6 + 6 + 2c = -18 + 6

Combine like terms: -6 + 6 = 0
0 + 2c = -18 + 6
2c = -18 + 6

Combine like terms: -18 + 6 = -12
2c = -12

Divide each side by '2'.
c = -6

Simplifying
c = -6

See similar equations:

| 3y-2x=1 | | 9(X-9)=-43.2 | | 4=g+1 | | (x^2)-x+1=0 | | 2(A+4)=11.2 | | (x^2)-5x=6 | | 4n-30=26 | | 0.3-0.03(x+1)=-0.05(1-x) | | 3(x+5)=-12 | | 3x-9y=54 | | -13n+14=40 | | 12y+4=8 | | 5x+8y=16 | | 2x+7+28=4x | | 1/2ln(y-1)-1/2ln(y+1)=1/2ln(x-1)-1/2ln(x+1) | | 4-(1/x)-(2/(x^2))=0 | | -3.3y=21.7 | | (3/4x^2)-(1/4x)-(1/2)=0 | | 12(2w-5)=4(6w+10) | | 20+8*0.5/20-x=12 | | 33-2x=6x+5 | | 7x+28=7x-14 | | -2x+6=-18+x | | 5(x+6)=40 | | (3x+40)+(2x-10)=180 | | -8y^2+4y-14=0 | | 6x-48+4x+9=180 | | 11a=0.088 | | 6E-3=25.2 | | y^4-33y^2+256=0 | | 6x-9+3x+24=180 | | 1/8=y/5 |

Equations solver categories